To some legal issues related to the participation of the Republic of Kazakhstan in the World Trade Organization - Karazhan, B.; Abdullin, A.I. (Bulletin of the Karaganda University “Law Series”, 2022)
The global economy has faced significant difficulties after the pandemic. The idea of the globalization of the world economy seems to be no longer encouraged by the superpowers. There is a growing trend of protectionism, so-called “economic nationalism” and the unification of different countries into regional economic unions. In this regard, the role of the World Trade Organization (WTO) in the field of international trade and the foreign economic activities of developing countries is increasing as the most recognizable and reputable international economic organization. The Republic of Kazakhstan is a member state of WTO since 2015. However, we see how trade-related conflicts are arising even in the Eurasian Economic Union (EAEU) area. This article suggests drawing attention to some bright problematic issues related to the presence of Kazakhstan in various economic integration associations. During this study, both official WTO documents and research papers of well-known international lawyers were studied. The results of the study will help shed light on the problems of ordinary people and can serve as an additional source of inspiration for the academic community.